Essential Oil Constituents of Leaves of the Male and FemaleShrubs of Juniperus chinensisL. from Isfahan: Essential oil of Juniperus chinensis179 - Suleiman Afsharypuor; Mohammadreza Rahiminezhad; Leili Ghaemmaghami; Majid Soleimani; Mohammadreza Khanmohammadi; Neda Afsharipour (Iranian Journal of Pharmaceutical Sciences, 2007)
The composition of essential oil of leaves of the male and female shrubs ofJuniperus chinensis L. (growing in Isfahan) was analyzed by gas choromatography(GC) and GC-mass spectrometery (MS). The main constituents of leaf oil of the maleshrub were: bornyl acetate (26.1%), sabinene (18.3%),trans-sabinyl acetate (11.1%),myrcene (9.2%), limonene (6.1%), elemol (5.5%), α-cadinol (2.3%), δ-cadinene(2.2%), trans-thujone (1.6%), α-pinene (1.3%) and α-muurolol (1.1%); while themajor constituents of leaf oil of the female shrub were: sabinene (18.0%), bornylacetate (12.3%), carotol (11.4%), elemol (9.9%), myrcene (8.8%), α-pinene (6.4%),δ-cadinol (4.8%), limonene (3.9%), δ-cadinene (3.4%) and α-muurolol (2.7%).